Genotype by environment interaction, path analysis, and yield stability of climate-resilient DroughtTEGO maize hybrids - Oyekunle, Muhyideen; Sserumaga, Julius Pyton; Adamu, Rabiu Salisu; Ndou, Eric; Beyene, Yoseph; Oikeh, Sylvester Ojo (Current Science Publishing, 2025)
The assessment of yield stability of climate-resilient DroughtTEGO® maize (Zea mays L.) hybrids is vital for the productivity and sustainability of maize production in Sub-Saharan Africa. This study evaluated the performance and environmental stability of DroughtTEGO® maize hybrids at multiple locations in Nigeria. Twenty one hybrids plus four checks were planted in an alpha lattice design with three replications for two years in nine locations. A combined analysis of variance revealed highly significant (P < 0.01) differences for most traits across years and locations, indicating the influence of environmental factors on the hybrid performance. Genotypic variability was observed for traits such as grain yield, plant height and flowering time, with hybrid × environment interactions significantly affecting hybrid rankings. Grain yield ranged from 3421 to 5808 kg ha⁻¹, with hybrid WE5229 outperforming commercial checks by 22.6%. Path analysis indicated that the number of ears per plant had the highest positive direct effect on yield, whereas ear aspect had the greatest negative impact. The GGE biplot analysis showed that PC1 and PC2 explained 53.41% of the total variation in grain yield, with WE9216 emerging as the most stable and highest-yielding hybrid across the locations. Ibadan and Birnin Kudu were identified as the best testing environments, whereas the other locations were useful for culling unstable hybrids. These results suggest that DroughtTEGO® hybrids, WE9216 and WE5229, are well-suited for commercialization in Nigeria. This study emphasizes the importance of multi-environment testing for identifying high-yielding and stable hybrids adapted to specific agro-ecologies.